The Index of Individuality Is Often a Misinterpreted Quantity Characteristic - Hyltoft Petersen, Per; Fraser, Callum G.; Sandberg, Sverre; Goldschmidt, Henk (Clinical chemistry and laboratory medicine, 1999)
The concept of the “index of individuality” was introduced by Eugene Harris in 1974. The index of individuality, calculated as (CVA 2 + CVI 2)1/2/CVG, where CvA, CvI, and CvG are analytical, within-subject, and between-subject coefficients of variation respectively, has been used by many to investigate the utility of conventional population-based reference values. For a high index of individuality, >1.4, it has been said that reference intervals will be more useful than for a low index, < 0.6. The validity of these concepts is investigated here and a number of our findings are at odds with the generally held opinion. The index of individuality has no impact on the fraction of individuals classified using population-based reference values, as long as the change in concentration from the usual state is of the same absolute magnitude and one sample is assayed to detect disease. However, when a measurement falling outside a reference limit is repeated in order to verify the finding, the index of individuality has considerable influence. For quantities with very low indices, the repeat test result, will be close to the first and give no new information, whereas for quantities with high indices, a repeat test will decrease the number of true positives and false positives.